Online corporate disclosure and informativeness of corporate earnings - Cai, Jiebing (2008)
The Internet has brought about a substantial change in the financial information environment and the costs of trading for investors. Our study examines the effects of online corporate disclosure on investors’ reactions to accounting earnings; in particular how publicly available corporate information, affects the trading volume volatility and returns volatility.